Investigating “Egusi” (Citrullus Colocynthis L.) Seed Oil as Potential Biodiesel Feedstock - Solomon, Giwa; Abdullah, Luqman Chuah; Adam, Nor Mariah (2010)
Biodiesel’s acceptance as a substitute for fossil-derived diesel has grown the world over. However, the food-fuel debate over conventional vegetable oils has rekindled research interest in exploring lesser known and minor oil crops. In this work, egusi melon seed oil was studied for the first time as a potential feedstock for biodiesel production. Crude egusi melon seed oil was transesterified using sodium methoxide as the catalyst at 60 °C and an oil/methanol ratio of 1:6 to produce its corresponding methyl esters. Egusi melon oil methyl ester (EMOME) yield was 82%. Gas chromatographic analysis of EMOME showed that it was composed mainly of palmitic, stearic, oleic, linoleic and linolenic esters, which is similar to the profile of sunflower, soybean and safflower oil. All the measured fuel properties of EMOME satisfied both the ASTM D6751 and the EN 14214 biodiesel standards. Fuel properties of EMOME were essentially identical with those of soybean, safflower and sunflower biodiesel. Remarkably, the kinematic viscosity of EMOME was measured to be 3.83 mm2/s, a value lower than most biodiesel fuels reported in the literature. The potential of egusi melon seed oil as a biodiesel feedstock is clearly presented in this study.